The Effect of Using the Drill Method in Learning Arabic Calligraphy to Improve the Writing Skills of Students in Indonesia - Falaqi Muhamad Rizal; Syuhadak; M. Abdul Hamid; Mohammad Samsul Ulum; Mamluatul Hasanah; R. Taufiqurrochman (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: This study examines the effect of using the drill method and the differences in learning outcomes of elementary school students in learning Arabic calligraphy. Methodology: The quasi-experimental design was used to determine the impact of the drill method on student learning. Then, the t-test was used to look for differences in students’ learning outcomes. A questionnaire was used to determine students’ interest in Arabic calligraphy. Findings: Based on the findings, the drill method in learning Arabic calligraphy creates a competitive atmosphere for elementary school students and positively affects students’ calligraphy writing skills. So, this research helps increase student achievement and enthusiasm for learning by applying the drill method in learning Arabic calligraphy. Implications/Novel Contribution: The novelty in this study is that this research becomes a basis and prototype for actualizing Arabic calligraphy learning. This research is the basis for developing every learning method in Arabic calligraphy, especially in Indonesia. Good Arabic calligraphy writing skills can become more creative and innovative so that it can provide students with skills for the future.